Locard Institute : What Harms You - Book 2 - Black, Lisa, 1963- (Thorndike, Maine : Center Point Large Print, 2024)
"The Locard Institute is a state-of-the-art forensic research center where experts from around the world come together to confront and solve the worlds most challenging and perplexing crimes. When Dr. Ellie Carr arrives for her first day as an instructor at the prestigious facility, the buildings glimmer amid the brilliant fall foliage on the shores of the Chesapeake Bay. But within hours a colleague, Dr. Barbara Wright, is found dead on the floor of a supply closet. Her death appears to be an accident -- but Ellie and her new supervisor, Dr. Rachael Davies, suspect a more sinister explanation. A young woman attending a professional training program then disappears, only to be found in a gruesome tableau. Other than their link to the Institute, there seems to be no connection between the student and Dr. Wright. Although forensic traces are elusive, Ellie and Rachael are determined to find the bizarre link between the violent and diverse deaths. As reporters shatter the privacy of Ellies new workplace, she searches old files and finds evidence of a crime that feels much too personal. But who, among those dedicated to justice, could be the threat? No matter how skilled she and Rachael may be in uncovering the truth, they may not be able to prevent a well-schooled killer from striking again."--
Keywords: Women forensic scientists -- Fiction; Women -- Crimes against; Fiction; Serial murder investigation -- Fiction; Serial murders -- Fiction; Forensic sciences -- Study and teaching; Fiction; Chesapeake Bay Region (Md. and Va.) -- Fiction; Thrillers (Fiction); Detective and mystery fiction; Psychological fiction; Large print books